New therapeutic options for HCV in Central Europe - Flisiak, Robert; Urbánek, Petr; Rokusz, Laszlo; Oltman, Marian; Makara, Mihaly; Janicko, Martin (Clinical and experimental hepatology, 2016)
New therapeutic options became available in 2015 in the European Union. We present the availability of interferon-free regimens with direct acting antivirals (DAA) in four Central European countries - the Czech Republic, Hungary, Poland and Slovakia - which despite similar historical, geographical and economic situations demonstrate different systems for access to anti-HCV (hepatitis C virus) medication. Treatment of patients in the Czech Republic was based in 2015 on an exceptional individual reimbursement procedure, but regular reimbursement procedures are expected in 2016. In Hungary the decision for treatment is balanced against budget limitations and the national Priority Index system reflecting stage of liver disease, activity of the disease and predictive factors. A reimbursed interferon (IFN)-free therapeutic program for all genotypes, without restrictions related to hepatic fibrosis and treatment history, is already available in Poland. In Slovakia patients with advanced fibrosis are currently selected for possible IFN-free therapy in 2016.
Keywords: treatment; Central Europe; HCV